PENGARUH LEADER MEMBER EXCHANGE (LMX) DAN KOMITMEN ORGANISASI TERHADAP KINERJA KARYAWAN DENGAN MEDIASI ORGANIZATION CITIZEN BEHAVIOUR (OCB) (Studi Kasus pada Karyawan Kospin Jasa Pekalongan) - Elshifa, Aria (Sekolah Tinggi Ilmu Ekonomi Dewantara, 2018)
Achieving corporate goals depends not only on modern equipment, facilities, and complete infrastructure, but it depends on the people who carry out the work. The success of an organization is strongly influenced by the performance of its employees. The purpose of this study to determine the level of employee performance in terms of the quality of superior relationships with subordinates (LMX) by taking the leadership character by employee and organizational commitment of employees through Organization Citizen Behaviour (OCB).The type of research used is the research of causality, research that aims to determine the relationship and the influence between two or more variables. The object of this research is Kospin Jasa Pekalongan.The results obtained: (1) Leader member Exchange effect on organizational citizenship Behaviour employees. (2) Organizational commitment has an effect on organizational citizenship Behaviour of Kospin Jasa Pekalongan. (3) Leader member Exchange affects the performance of employees of Kospin Jasa Pekalongan. (4) Organizational commitment affects the performance of employees of Kospin Jasa Pekalongan. (5) Organizational citizenship Behaviour affects the performance of employees of Kospin Jasa Pekalongan. (6) Leader member exchange has an indirect effect on employee performance through organizational citizenship Behaviour of Kospin Jasa Pekalongan. (7) Organizational commitment has an indirect effect on employee performance through organizational citizenship Behaviour of Kospin Jasa Pekalongan.